2002
DOI: 10.1002/1099-0690(200211)2002:21<3604::aid-ejoc3604>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Distamycin Analogues without Leading Amide at Their N-Termini − Comparative Binding Properties to AT- and GC-Rich DNA Sequences

Abstract: An efficient, simple and general route towards the solutionphase synthesis of four distamycin analogues containing 2−5 N-methylcarboxamide units without the leading amide unit at the N-terminus is described. The binding abilities of these molecules to calf thymus DNA, poly d(AT), poly dA.poly dT and poly d(GC) were evaluated by duplex DNA melting temperature (T m ) analysis, fluorescence probe displacement assay, footprinting studies and induced circular dichroism (ICD) measurements. A minimum of three N-methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Synthesis and evaluation of distamycin analogues without the leading amide unit at the N-terminus demonstrated that a hydrogen bond donors or acceptor atom per se at the N-terminus is not essential for their DNA binding, however a minimum of three pyrrole carboxamide units is necessary for the onset of DNA binding [ 13 , 14 ]. Interestingly, intense induced circular dichroism (ICD) spectra were obtained not only with AT-rich DNA tracts, but also with poly d(GC), even in such salt concentrations of the solution, at which poly d(GC) is likely to exist in the Z conformation [ 15 , 16 ]. These results confirmed the involvement of polyamide-based minor groove binders in gene regulation processes and showed that thus subtle modifications in the ligand molecular structure can have dramatic effect on their DNA binding properties.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis and evaluation of distamycin analogues without the leading amide unit at the N-terminus demonstrated that a hydrogen bond donors or acceptor atom per se at the N-terminus is not essential for their DNA binding, however a minimum of three pyrrole carboxamide units is necessary for the onset of DNA binding [ 13 , 14 ]. Interestingly, intense induced circular dichroism (ICD) spectra were obtained not only with AT-rich DNA tracts, but also with poly d(GC), even in such salt concentrations of the solution, at which poly d(GC) is likely to exist in the Z conformation [ 15 , 16 ]. These results confirmed the involvement of polyamide-based minor groove binders in gene regulation processes and showed that thus subtle modifications in the ligand molecular structure can have dramatic effect on their DNA binding properties.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds 1a – c [79][80] and propargylated cyclam[81] were prepared according to literature methods (Scheme S1 and Text S1). Four aspects of these structures are of interest in comparison to literature lexitropsins: a) lack of the N -terminal formamido group, b) attachment of an unprecedented group (cyclam) to the C terminus, c) inclusion of an alkyl spacer between the azamacrocycle and the recognition motif and d) complexation of metal ions (copper and zinc).…”
Section: Resultsmentioning
confidence: 99%
“…DNA binding studies with small molecules are very sensitive to the salt concentration of the solution [65], [79][80], [92]. HEPES buffer was chosen for all experiments based on literature precedents [63], [93]…”
Section: Resultsmentioning
confidence: 99%
“…This compound's lack of binding was not surprising, as it has previously been reported that polyamides with three heterocycles exhibit the strongest binding properties, whereas compounds with two heterocycles display greatly reduced binding. 13,14 The DNA interaction properties of benzamidine containing polyamide 1 were further investigated by surface plasmon resonance (SPR) in which the binding constant could be determined. Based on the best fit of the sensorgrams, the kinetics of association and dissociation were obtained, and from these values the binding constant was calculated to be 8 χ 10 s M" 1 .…”
Section: Heterocyclic Communicationsmentioning
confidence: 99%